CONSTRUCTION OF MEANING IN RADEN SAPU JAGAD RITUAL IN KAWI MOUNTAIN - RINALDI, ADINDA MUSTIKA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Raden Sapu Jagad Ritual, Mukso, Premonition Raden Sapu Jagad is the nobleman who is very religious and has highest levelof supranatural ability. Raden Sapu Jagad had experienced Mukso or the ability to live in 2 worlds. Because of that, until now there are a lot of people believe that Raden Sapu Jagad still alive around Kawi Mountain. The people believe if they can conduct inner interaction with him, they can get some premonitions to increase their jobs degree. However, only unmarried women/ single female can perform this ritual directly. The writer wants to uncover this phenomenon deeper about the construction of meaning Raden Sapu Jagad ritual process.This study uses qualitative approach in relation to the use of clear andsystematic description about the phenomena being studied. Descriptive study inobservation and open interview with ritual expert and the performer of this ritual is applied in this study to analyze the meaning of ritual procession and about women’s role in this ritual.This study reveals that all the meaning of ritual procession have correlationswith women’s role in this ritual. Women considered as a holy creatures and lofty one who is proper to get some premonitions from Raden Sapu Jagad. This phenomenon becomes stronger because of folk-belief theory. That is about belief concept that influences to validate the data of this research which is talking about supernatural in ritual.The writer suggests English Department students learn more about socialculture concepts that exist in our environments. The writer also suggests the next researcher conduct their analysis about cultural phenomenon and try to link up with literary works.